The Effect of Practicum-Integrated Discovery Learning Model on Students' Procedural Knowledge of Microscope Use and Cell Structure Observation - Solehat, Solehat; Purwanti, Wiwit; Murni, Dewi; Rahman, Aris (Jurnal Pendidikan Abad Ke-21, 2025)
Having procedural knowledge empowers students and helps them connect theory and practice in biology education.  Encouraging pupils to learn procedural knowledge helps them acquire academic talents and practical life skills.  In fact, many studies show that students' procedural knowledge is still low, especially regarding the use of microscopes and cell observation. This study aims to discover how the Discovery Learning model, combined with practicum, affects students' procedural understanding of using microscopes and seeing cell structures.  A pretest-posttest control group design was employed in this quantitative quasi-experimental study.  The pupils of Class XI at one of the senior high schools in Pandeglang, Banten comprised the research population.  Seventy-four students were chosen at random to make up the research sample.  Two groups—the experimental and control class groups—were created from the research sample. Students in the control class utilized the Discovery learning model without practicum activities, while students in the experimental class used the Discovery learning model combined with practicum activities.  According to the findings, students in the experimental class outperformed those in the control class regarding their average post-test score on procedural knowledge.  Additionally, pupils in the experimental class had a greater improvement in procedural knowledge.  Students' comprehension of scientific topics is strengthened by combining discovery learning with practicum. Additionally, students become more involved in the learning process, which boosts their procedural knowledge. Students in the experimental class were more actively engaging in each activity stage, according to the observation data from the practicum.  This result demonstrates how students' procedural knowledge and learning outcomes are enhanced when discovery learning and practicum are combined.  Therefore, in order to enhance students' procedural understanding, teachers had to increase the frequency of practicums.